Fair warning [compact disc, unabridged] - Connelly, Michael, 1956- (Connelly, Michael, 1956 - Jack McEvoy, 2020)
Veteran reporter Jack McEvoy makes a shocking discovery that connects a crime to other mysterious deaths across the country. But his inquiry hits a snag when he himself becomes a suspect.